Vasopressin Bolus Protocol Compared to Desmopressin (DDAVP) for Managing Acute, Postoperative Central Diabetes Insipidus and Hypovolemic Shock - Anukrati Shukla; Syeda Alqadri; Ashley Ausmus; Robert Bell; Premkumar Nattanmai; Christopher R. Newey (Case Reports in Endocrinology)
Introduction. Management of postoperative central diabetes insipidus (DI) can be challenging from changes in volume status and serum sodium levels. We report a case successfully using a dilute vasopressin bolus protocol in managing hypovolemic shock in acute, postoperative, central DI. Case Report. Patient presented after bifrontal decompressive craniotomy for severe traumatic brain injury. He developed increased urine output resulting in hypovolemia and hypernatremia. He was resuscitated with intravenous fluids including a dilute vasopressin bolus protocol. This protocol consisted of 1 unit of vasopressin in 1 liter of 0.45% normal saline. This protocol was given in boluses based on the formula: urine output minus one hundred. Initial serum sodium was 148 mmol/L, and one-hour urine output was 1 liter. After 48 hours, he transitioned to 1-desamino-8-D-arginine vasopressin (DDAVP). Pre-DDAVP serum sodium was 149 mmol/L and one-hour urine output 320 cc. Comparing the bolus protocol to the DDAVP protocol, the average sodium was 143.8 ± 3.2 and 149.6 ± 3.2 mmol/L (p=0.0001), average urine output was 433.2 ± 354.4 and 422.3 ± 276.0 cc/hr (p=0.90), and average specific gravity was 1.019 ± 0.009 and 1.016 ± 0.01 (p=0.42), respectively. Conclusion. A protocol using dilute vasopressin bolus can be an alternative for managing acute, central DI postoperatively, particularly in setting of hypovolemic shock resulting in a consistent control of serum sodium.